Нові квазіатомні наноструктури, що містять екситонні квазімолекули і екситонні квазікристали: теорія - Покутній, С. І. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2019)
In review, deals with the theory of exciton quasimolecules in a nanoheterostructures. It has been found that the formation of a exciton quasimolecule in a nanoheterostructures made up of aluminum oxide quantum dots synthesized in a dielectric matrix is of threshold character and can occur in a nanosystem where the distance D between the surfaces of quantum dots is given by the condition . The existence of such distance arises from quantum size effects in which the decrease in the energies of interaction of the electrons and holes entering into the Hamiltonian of the “exciton molecule” with decrease of the distance D between the surfaces of the QD cannot compensate for the increase in the kinetic energy of the electrons and holes. At larger distances D between the surfaces of quantum dots: the biexciton breaks down into two excitons (consisting of spatially separated electrons and holes), localized over QD surfaces. It was shown that the convergence of two quantum dots up to a certain critical value between surfaces of quantum dot lead to overlapping of electron orbitals of superatoms and the emergence of exchange interactions. In this case the overlap integral of the electron wave functions takes a significant value. As a result, the conditions for the formation of quasi-molecules from quantum dots can be created. We have shown that in such a nanoheterostructures acting as “exciton molecules” (biexcitons consisting of spatially separated electrons and holes) are the quantum dots of aluminum oxide with excitons localizing over their surfaces. The position of the biexciton state energy band depends both on the mean radius of the quantum dots, and the distance between their surfaces, which enables one to purposefully control it by varying these parameters of the nanostructure. As our variational calculations show, the interaction of the excitons with the surfaces of quantum dots (“intramolecular” interaction) is much stronger than that between quantum dots (“intermolecular” interaction). Due to the translational symmetry of such a nanoheterostructures of quantum dots, it permits propagation of electronic excitation in the form of biexcitons. As follows form the results of the variational calculations, the major contribution to the biexciton binding energy is from the energy of exchange interaction of electrons and holes, which by far surpasses that from their Coulomb interaction. It is established that at constant concentrations of biexcitons at temperatures T below a certain critical temperature Tc due to the radiative annihilation of one of the excitons forming a biexciton one can expect a new spectral band of luminescence shifted relative to the exciton band by the biexciton binding energy . This new luminescence band disappears at temperatures above Tc. At a constant temperature Т < Tc the growth of exciton concentration brings about weakening of the exciton band and strengthening of the biexciton band of luminescence.